(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article describes the social significance of protecting the environment, and its coverage of Judaism, Christianity and Islam. The path set by Judaism, Christianity and Islam in ensuring social stability is primarily in the interests of the people, and this principle presupposes that mankind will live a spiritually, economically and medically sound life.